Los costos de producción y su incidencia en el margen bruto de la Empresa Inducalidad S.A. - Leiva Veloz, Sandra Verónica (2019)
The present investigation titled "The costs of production and its incidence in the gross margin of the company INDUCALIDAD S.A." has as a general objective to know how the production activities affect the gross margin of the entity and propose a solution for its improvement. Analyzing the theories related to cost control systems, it was found that the company manages a system by production processes, which is not considered efficient for the type of work that is carried out in the entity…...